2014
DOI: 10.1037/cfp0000026
|View full text |Cite
|
Sign up to set email alerts
|

Examining parental denigration behaviors of co-parents as reported by young adults and their association with parent–child closeness.

Abstract: Over the past 30 years, number researchers have documented that interparental conflict predicts (predicts) adjustment difficulties among children from divorced and married families, as well as strained parent-child relationships. The conflict literature, reports of "parental alienation" behaviors, and clinical experience make it clear that some parents make disparaging comments about their coparent in front of their children. Very little empirical research has been conducted on the actual behaviors involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
4
25
0
1
Order By: Relevance
“…The current study's findings about the relationship between levels of interparental conflict and adult children's perceptions of relational ethics support prior research (e.g. Amato and Sobolewski, ; Riggio and Valenzuela, ; Rowen and Emery, ) demonstrating that participants’ reports of higher levels of interparental conflict were associated with poorer relationships with parents. In a study by Fosco and Grych (), adolescents who reported being triangulated into their parents’ conflict reported poorer relationships with their parents over time and increased self‐blame for their parents’ conflict.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The current study's findings about the relationship between levels of interparental conflict and adult children's perceptions of relational ethics support prior research (e.g. Amato and Sobolewski, ; Riggio and Valenzuela, ; Rowen and Emery, ) demonstrating that participants’ reports of higher levels of interparental conflict were associated with poorer relationships with parents. In a study by Fosco and Grych (), adolescents who reported being triangulated into their parents’ conflict reported poorer relationships with their parents over time and increased self‐blame for their parents’ conflict.…”
Section: Discussionsupporting
confidence: 55%
“…Supporting the long‐lasting nature of conflict on adult children's relationships with their parents, Riggio and Valenzuela () determined in a study of Latino‐American undergraduate students that recollections of higher levels of interparental conflict were associated with poorer relationships with both mothers and fathers. In addition, Rowen and Emery () found a significant relationship between the presence of parental denigration – speaking in a demeaning way about a co‐parent – and adult children's reports of a lack of trust, poor communication quality, and emotional isolation in their relationships with both parents. Thus, parental conflict affects children in their youth and into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, denigration was moderately correlated with young adult children's ratings of conflict, suggesting that these are related but distinct constructs. Overall, these findings are consistent with previous work (Rowen & Emery, ) and suggest that denigration occurs across marital status and is important to assess in work with families, especially in the case of divorce.…”
Section: Discussionsupporting
confidence: 90%
“…Together with the results from a previous study of another large sample (Rowen & Emery, ), the present findings indicate that when one parent puts down the other to his or her children, the overwhelming effect at the group level is for children to feel more distant from the parent who makes disparaging comments. In short, denigration has a boomerang effect.…”
Section: Discussionsupporting
confidence: 79%
“…The term “parental denigration” refers to one parent directly disparaging or speaking negatively about the other parent to, or in front of, his/her children (Rowen & Emery, ). This behavior is of interest for two reasons.…”
mentioning
confidence: 99%